A highly efficient Cu-catalyst system for N-arylation of azoles in water - Wang, Deping; Zhang, Fuxing; Kuang, Daizhi; Yu, Jiangxi; Li, Junhua (Green chemistry : an international journal and green chemistry resource : GC, 2012)
6,7-Dihydroquinolin-8(5H)-one oxime (L3) was found to serve as a superior ligand for the CuI-catalyzed N-arylation of imidazoles with aryl iodides, bromides, and electron-deficient chlorides in water. Moreover, the CuI/L3 catalyst system enabled the coupling reactions to take place smoothly with high yields under a low catalyst loading (0.1-1 mol% CuI and 0.2-2 mol% L3).